The Effect of Wudhu Spiritual Therapy in Controlling Emotions in Patients at Risk of Violent Behavior - Biahimo, Nur Uyuun I; Firmawati; Syukur, Sabirin; Mawikere, Irma Novriyani (Jurnal Berita Ilmu Keperawatan, 2024)
In the Limboto Health Centre working area, the behavioral changes of patients at risk of violent behavior were found to be that these patients had never received spiritual ablution therapy and were only given medication as prescribed or recommended. Mental disorders affect 970 million people worldwide. This study aims to determine whether ablution spiritual healing helps patients at risk of violent behavior in the Limboto Health Centre working area to control their emotions. Pre exploratory examination plan with one collection pretest-posttest configuration approach, the population of patients in danger of violent behavior in the working area of Limboto Community Group Welfare Centre, number of tests 15 people with complete examination procedures, information collected using the perception of signs and side effects sheet of patients in danger of violent behavior and tried using matched t-test measured parametric test. Results showed that before being given medication for otherworldly bathing treatment, all patients gave indications and side effects that generally appear in patients in danger of violent behavior. Still, after intercession, patients have the option to get mediation. control their feelings after being given bathing treatment given the consequences caused by paying attention to the symptoms and side effects. The p.value obtained from the paired t-test was 0.001 which is smaller than the value of 0.05. It was established in the Limboto Health Centre working area that the spiritual therapy of ablution helps patients at risk of violent behavior to control their emotions. Therefore, the health center is expected to support medical treatment to achieve more effective results in addition to using medical therapy which includes the administration of drugs